2012
DOI: 10.1136/bjophthalmol-2011-301370
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine induces oxidative stress in young adult central retinal vein occlusion

Abstract: TBARS and homocysteine are known to be independent risk factors for CRVO. TBARS can be influenced by both homocysteine and TAC, thereby contributing to the aetiopathology of CRVO by increasing oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Wang et al [27] showed a significant association between serum homocysteine and oxidative stress in elderly patients with obstructive sleep apnea syndrome. It was also demonstrated that homocysteine increased the oxidative stress levels dose-and time-dependely in cultured bovine retinal endothelial cells [28]. These findings might be consistent with our present finding indicating that plasma total homocysteine levels were correlated with plasma 8-iso-PG F2α levels.…”
Section: Relationship Between Membrane Fluidity Of Red Blood Cells Ansupporting
confidence: 93%
“…Wang et al [27] showed a significant association between serum homocysteine and oxidative stress in elderly patients with obstructive sleep apnea syndrome. It was also demonstrated that homocysteine increased the oxidative stress levels dose-and time-dependely in cultured bovine retinal endothelial cells [28]. These findings might be consistent with our present finding indicating that plasma total homocysteine levels were correlated with plasma 8-iso-PG F2α levels.…”
Section: Relationship Between Membrane Fluidity Of Red Blood Cells Ansupporting
confidence: 93%
“…In most of these cases, CRVO occurs without the presence of the typical risk factors, and a comprehensive workup is warranted [2]. Unusual causes for CRVO in young patients include hypercoagulability states, collagen vascular diseases, lymphoproliferative disorders, malignant hypertension, medications (most notably oral contraceptives and isotretinoin), and trauma [2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13]. A recent study has demonstrated that hyperlipidemia and hyperhomocysteinemia were the most significant risk factors for CRVO in patients under 40 [14].…”
Section: Introductionmentioning
confidence: 99%
“…We observed this in our earlier study in CRVO. 47 Thus, Hcy and its metabolite, HcyTL, affect protein function through homocysteinylation. 17 There is oxidative stress and poor oxidant defence in ED.…”
Section: Discussionmentioning
confidence: 99%